miRNA-26a-5p Accelerates Healing via Downregulation of PTEN in Fracture Patients with Traumatic Brain Injury - Yuan Xiong; Faqi Cao; Liangcong Hu; Chenchen Yan; Lang Chen; Adriana C. Panayi; Yun Sun; Wu Zhou; Peng Zhang; Qipeng Wu; Hang Xue; Mengfei Liu; et al. (Elsevier, 2019)
Patients who sustain a traumatic brain injury (TBI) are known to have a significantly quicker fracture healing time than patients with isolated fractures, but the underlying mechanism has yet to be identified. In this study, we found that the upregulation of miRNA-26a-5p induced by TBI correlated with a decrease in phosphatase and tensin homolog (PTEN) in callus formation. In vitro, overexpressing miRNA-26a-5p inhibited PTEN expression and accelerated osteoblast differentiation, whereas silencing of miRNA-26a-5p inhibited osteoblast activity. Reduction of PTEN facilitated osteoblast differentiation via the PI3K/AKT signaling pathway. Through luciferase assays, we found evidence that PTEN is a miRNA-26a-5p target gene that negatively regulates the differentiation of osteoblasts. Moreover, the present study confirmed that preinjection of agomiR-26a-5p leads to increased bone formation. Collectively, these results indicate that miRNA-26a-5p overexpression may be a key factor governing the improved fracture healing observed in TBI patients after the downregulation of PTEN and PI3K/AKT signaling. Upregulation of miRNA-26a-5p may therefore be a promising therapeutic strategy for promoting fracture healing. Keywords: traumatic brain injury, fracture, miRNA, PTEN